Tetrac Delayed the Onset of Ocular Melanoma in an Orthotopic Mouse Model - Ashur-Fabian, Osnat; Zloto, Ofira; Fabian, Ina; Tsarfaty, Galya; Ellis, Martin; Steinberg, David M.; Hercbergs, Aleck; Davis, Paul J.; Fabian, Ido Didi (Frontiers in Endocrinology, 2019)
Ocular melanoma research, the most common primary intraocular malignancy in adults, is hindered by limited in vivo models. In a series of experiments using melanoma cells injected intraocularly into mouse eyes, we developed a model for ocular melanoma. Inoculation of 5x105 B16F10 cells led to rapid tumor growth, extensive lung metastasis and limited animal survival, while injection of 102 cells was sufficient for intraocular tumors to grow with extended survival. In order to improve tumor visualization, 102 melanoma cells (B16F10 or B16LS9) were inoculated into Balb/C albino mouse eyes. These mice developed intraocular tumors that did not metastasize and exhibited extended survival. Next, we studied the therapeutic potential of inhibitors of the thyroid hormones-alphavbeta3 integrin signaling pathway in ocular melanoma. By utilizing tetraiodothyroacetic acid (tetrac), a thyroid hormone derivative, a delay in tumor onset in the B16F10 (integrin+) arm was observed, compared to the untreated group, while in the B16LS9 cells (integrin-) a similar rate of tumor onset was noticed in both experimental and control groups. In summary, following an optimization process, mouse ocular melanoma model were developed. The models exhibited an extended therapeutic window and can be utilized as a platform for investigating various drugs and other treatment modalities